2008
DOI: 10.1097/ccm.0b013e318186b9ce
|View full text |Cite
|
Sign up to set email alerts
|

Presence of electroencephalogram burst suppression in sedated, critically ill patients is associated with increased mortality

Abstract: Objectives This study investigates the possibility of a relationship between oversedation and mortality in mechanically ventilated patients. The presence of burst suppression, a pattern of severely decreased brain wave activity on the electroencephalogram, may be unintentionally induced by heavy doses of sedatives. Burst suppression has never been studied as a potential risk factor for death in patients without a known neurologic disorder or injury. Design: Post hoc analysis of a prospectively observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(95 citation statements)
references
References 39 publications
3
90
0
2
Order By: Relevance
“…Whereas burst suppression is sometimes a therapeutic goal in the treatment of refractory status epilepticus, burst suppression resulting from deep sedation or metabolic derangements during critical illness is nearly always inadvertent and has been shown to be an independent predictor of death [36, 37]. Thus, avoiding burst suppression via EEG monitoring may improve outcomes for deeply sedated ICU patients.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas burst suppression is sometimes a therapeutic goal in the treatment of refractory status epilepticus, burst suppression resulting from deep sedation or metabolic derangements during critical illness is nearly always inadvertent and has been shown to be an independent predictor of death [36, 37]. Thus, avoiding burst suppression via EEG monitoring may improve outcomes for deeply sedated ICU patients.…”
Section: Introductionmentioning
confidence: 99%
“…During general anesthesia with ether-derived volatile agents, the EEG often shows a dominance of delta waves (0-4 Hz) coupled with theta waves (4-8 Hz) and/or alpha (8-12 Hz) and low-beta (12)(13)(14)(15)(16) oscillations. 7 Patients with increased low-frequency EEG activity during the rewarming phase of cardiac surgery are at increased risk for postoperative complications, including delirium.…”
Section: Introductionmentioning
confidence: 99%
“…SR can appear when there is cerebral hypoxaemia or when anaesthesia is too deep. Watson et al observed that the presence of SR was related to increased mortality in critically ill patients and emphasized the prognostic significance of SR. 14 Although BIS monitoring is limited to the unilateral frontal cortex and values are affected by variety of clinical situation, 15 it may give the chance to detect critical changes of cerebral perfusion. 16 For a better monitoring of cerebral perfusion in high-risk cases, the full EEG monitoring during surgery might be the best.…”
Section: Discussionmentioning
confidence: 99%